PELATIHAN MENGGUNAKAN CANVA GUNA MENINGKATKAN MINAT DAN MOTIVASI BELAJAR - Arnidha, Yunni; Adi Puspito, Dhimas Rinda (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2023)
The background of this community service is the low interest and motivation of students in learning mathematics. The low interest and learning motivation of students, especially in learning mathematics, results in students being lazy to learn mathematics. Mathematics is one of the subjects that is considered quite difficult and even very difficult to learn. This is because the math teacher is fierce and the teacher doesn't do the learning according to the character of the students. To assist in increasing students' interest and learning motivation, especially in mathematics, the author made an effort to make Booktalk, part of the e-module designed by prioritizing the character of students. The author uses the method of developing mathematics learning by utilizing the Canva application, where through this application, educators are taught to develop modules into Booktalk so that learning activities can provide new experiences for students and can increase students' interest and motivation in learning mathematics.